2017
DOI: 10.1016/j.cogpsych.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Parallel interactive retrieval of item and associative information from event memory

Abstract: Memory contains information about individual events (items) and combinations of events (associations). Despite the fundamental importance of this distinction, it remains unclear exactly how these two kinds of information are stored and whether different processes are used to retrieve them. We use both model-independent qualitative properties of response dynamics and quantitative modeling of individuals to address these issues. Item and associative information are not independent and they are retrieved concurre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 114 publications
(148 reference statements)
3
42
0
Order By: Relevance
“…This similarity could arise either because items and associations are encoded using similar information or because the processes used to retrieve item and associative information are related, or both. We are not in a position to adjudicate this question here, although we note that other work from our laboratory supports the idea that item and associative information are both stored and retrieved using similar processes (Cox & Criss, 2017), and that memory for associative information involves elaborating or interrelating information about items (Cox & Shiffrin, 2017;see also McGee, 1980;Dosher, 1984;Dosher & Rosedale, 1989, 1991, 1997. Consistent with the idea that item and associative information are encoded in a similar manner, we found that the same item properties, like concreteness and semantic specificity, that make a single word easy to recognize (and to reject when unstudied) also make it easy to recognize a pair in which that word appears.…”
Section: Theoretical Implicationsmentioning
confidence: 73%
“…This similarity could arise either because items and associations are encoded using similar information or because the processes used to retrieve item and associative information are related, or both. We are not in a position to adjudicate this question here, although we note that other work from our laboratory supports the idea that item and associative information are both stored and retrieved using similar processes (Cox & Criss, 2017), and that memory for associative information involves elaborating or interrelating information about items (Cox & Shiffrin, 2017;see also McGee, 1980;Dosher, 1984;Dosher & Rosedale, 1989, 1991, 1997. Consistent with the idea that item and associative information are encoded in a similar manner, we found that the same item properties, like concreteness and semantic specificity, that make a single word easy to recognize (and to reject when unstudied) also make it easy to recognize a pair in which that word appears.…”
Section: Theoretical Implicationsmentioning
confidence: 73%
“…One of the defining features of episodic memory is that its content involves associating multiple elements, often including the who, what, and where of an event. As such, the content of episodic memory involves both items (people, places, objects, feelings) and the associations between those items (e.g., Cox & Criss, 2017Kahana, Howard, & Polyn, 2008;Murdock, 1982;Tulving, 1972). Associations matter; our capacity to explicitly relate objects and their meaning and to relate context and items (events/people) is at the heart of learning and memory (e.g., Anderson & Bower, 1973;Zacks & Tversky, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one of the signatures of normal cognitive aging is a loss in the capacity to create new associations between items − a phenomenon known as the age-related associative deficit (Naveh-Benjamin, 2000). Although most agree on the importance of associative memory, our understanding of the nature of associations and how they relate to item information is still very limited (Cox & Criss, 2017Cox & Shiffrin, 2017). It follows that a better understanding of associative memory will support the development of memory theory and contribute to our understanding of important issues such as normal and abnormal cognitive aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, there are still a variety of ways that ensembles might interact with one another. Although inhibitory interactions between accumulators are common in some computational models of decision making (e.g., Boucher, Palmeri, Logan, & Schall, 2007;Mordkoff & Yantis, 1991;Purcell et al, 2012;Usher & McClelland, 2001) and have been explored in ensemble models (Wong & Wang, 2006), facilitatory interactions are also eminently plausible, particularly in situations where alternatives are similar to one another or are based on similar sources of evidence (Busemeyer & Townsend, 1993;Cox & Criss, 2017Townsend & Wenger, 2004). As with our explorations of correlated within-trial variability within an ensemble, exploring the all the ways in which ensembles might interact with one another would be a complex undertaking, but the results presented here can help guide research along these lines by helping to exclude certain model variants that are a priori implausible with respect to describing the neural underpinnings of decision making.…”
Section: Perspectives and Extensionsmentioning
confidence: 99%